Digital strolls using UniCDent toolkit-part 2: reimagining the walking method for online participation - Eachempati, Prashanti; Martin, John; Hanks, Sally; Nasser, Mona (Frontiers in Oral Health, 2025)
Distance and remoteness no longer pose barriers to conducting meaningful research, as the adaptation of participatory methods can address these challenges effectively. This article examines the transformation of the UniCDent Toolkit, originally designed to capture patients' perceptions of uncertainty in dental environments, for online participatory interactions with dentists. The toolkit, which uses the walking method, incorporates components such as imagery, gallery walks, quadrant mapping, and trade-offs to explore uncertainty in dental practice. Initially, dentists expressed discomfort in sharing their uncertainty in a group setting, prompting a shift to an online format that maintained participant engagement and created a safe space for open dialogue. Each component was carefully tailored for the virtual setting: dentists documented their uncertainty using auto-photography, shared insights through a structured slide walk, collaboratively mapped their uncertainty with a virtual grid, and participated in trade-off discussions using Mentimeter polling. This process highlights the importance of adapting participatory methods to meet the needs of remote participation, while preserving the participatory ethos. We provide an example of such an adaptation, demonstrating how the UniCDent Toolkit which was initially designed for dental environments can be applied to various healthcare settings and research questions.